Application of K-Means Clustering Algorithm to Obtain Recommendations for Strategies to Increase the Number of Students in the Information Systems Study Program at ITB Ahmad Dahlan Jakarta - Diana Yusuf; Xie Guilin; Deng Jiao (Journal of Computer Science Advancements, 2023)
The rapid development of technology today has almost touched all sectors of life such as the economy, health and education. The technology currently used produces a lot of data every day, one of which is in the field of education. Data mining is a group of methods used to investigate and reveal complex relationships in very large data sets. Data here means information organized in a tabular format, as is often used in relational database management. This research uses data from the academic section of ITB Ahmad Dahlan, namely data on students of the Information Systems study program from 2019 to 2022. The attributes that will be used for this research are student gender, student employment status and student achievement index.  Recommendations for promotional strategies to increase the number of new students are to conduct visits to high schools or vocational schools. Not only that, the new student admission team can also promote to companies or offices.